The Triumvirate rei publicae constituendae, ἀντάρχοντες in an Inscription from Aphrodisias, and the Late Republican Promagistracy - Frolov, Roman M. (Gerión. Revista de Historia Antigua, 2024)
This paper begins with an overview of some of the difficulties with modern conceptions – as formulated especially by Ugo Coli, Frederik Vervaet, and Carsten Lange – of the Triumvirate rei publicae constituendae as an instance of the so-called magistracies ad tempus incertum. According to these scholars, the Triumvirate could be legally retained past the term stipulated by statutory provisions. Drawing upon the notion that the contemporaries perceived the Triumvirate as a temporary formalization of personalized informal power, which would persist and effectively control both the sphere militiae and the sphere domi even after its holders ceased to be triumvirs and formally became promagistrates, this paper puts forth a hypothesis to elucidate the use of the term ἀντάρχοντες (typically denoting promagistrates) in an Aphrodisias inscription from ca. 39/38 BCE. In this text, ἀντάρχοντες refers to those who could convene the Roman Senate. The understanding of the Triumvirate holds pivotal significance as a prerequisite for any interpretation of this inscription, but the latter tells us more about the Realpolitik of the late republican promagistracy than the formalities of the Triumvirate. In unraveling the reasons for which the inscription attributes to the ἀντάρχοντες the authority that promagistrates never formally possessed, we must account for the possibility that the text collapses one’s legal rights and statuses from distinct temporal contexts and one’s capacity to take informal political initiative, into a single construction. However, this reading becomes plausible only when we take into consideration the previous experience of the Romans and provincials with some powerful promagistrates interfering with Roman city politics.